DEIXIS ANALYSIS IN THE SONG LYRICS “ALL GIRLS ARE THE SAME” BY JUICE WRLD - Ni Luh Putu Desy Sukmarini; I Gusti Ayu Mahatma Agung (PROJECT (Professional Journal of English Education), 2023)
The purpose of this study is to identify the types and meaning of deixis in Juice Wrld’s song “All Girls Are the Same”. The descriptive qualitative method was used in this study. The data was collected using a number of procedures. The researchers listened to the song on Spotify in the initial phase. Next, the researchers searched the internet for the lyrics of the song “All Girls Are The Same.” Subsequently, the deictic words in the song lyrics were analyzed. Ultimately, the data was categorized into several categories by the researchers based on their selected hypothesis. Theoretical framework proposed by Yule (1996) was applied to analyze the data. Based on the analysis, this study found 67 deixis, which are personal deixis, spatial deixis, and temporal deixis. The total frequency of deixis in the lyrics of "All Girls Are The Same" is 67, with 56 deictic words or 83,58% from personal deixis, 4 deictic words, or 5,97% from temporal deixis, and 4 deictic words, or 10,45% from spatial deixis. The word "I" is the most prevalent word in the lyrics of “All Girls Are The Same”, making personal deixis the most frequently used deixis in those lyrics.